2021
DOI: 10.3389/fnagi.2020.597491
|View full text |Cite
|
Sign up to set email alerts
|

Visual Abnormalities Associate With Hippocampus in Mild Cognitive Impairment and Early Alzheimer's Disease

Abstract: Background and Objective: Alzheimer's disease (AD) has been shown to affect vision in human patients and animal models. This study was conducted to explore ocular abnormalities in the primary visual pathway and their relationship with hippocampal atrophy in patients with AD and mild cognitive impairment (MCI). The aim of this study was to investigate the potential value of ocular examinations as a biomarker during the AD progression.Methods: Patients with MCI (n = 23) or AD (n = 17) and age-matched cognitively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…However, the hippocampus (HP), a key cortical structure regulating cognitive processes such as learning and memory (Broadbent et al, 2004 ; Kumaran and Maguire, 2005 ; Hannula et al, 2013 ) also resulted affected in BBSOAS patients. Due to the central role of the HP in controlling key cognitive skills, even small developmental defects can have a dramatic impact on behavioral performances (Mátéffyová et al, 2006 ; Ramos, 2008 ; Wan et al, 2021 ; Zhao et al, 2021 ). While the dorsal hippocampal pole is more involved in spatial navigation (Moser et al, 1995 ), the ventral one controls non-spatial learning and emotional behaviors (Kheirbek et al, 2013 ; Wang et al, 2013 ).…”
Section: Beyond the Neocortex: Nr2f1 Regulates The Anatomical And Functional Development Of The Hippocampusmentioning
confidence: 99%
“…However, the hippocampus (HP), a key cortical structure regulating cognitive processes such as learning and memory (Broadbent et al, 2004 ; Kumaran and Maguire, 2005 ; Hannula et al, 2013 ) also resulted affected in BBSOAS patients. Due to the central role of the HP in controlling key cognitive skills, even small developmental defects can have a dramatic impact on behavioral performances (Mátéffyová et al, 2006 ; Ramos, 2008 ; Wan et al, 2021 ; Zhao et al, 2021 ). While the dorsal hippocampal pole is more involved in spatial navigation (Moser et al, 1995 ), the ventral one controls non-spatial learning and emotional behaviors (Kheirbek et al, 2013 ; Wang et al, 2013 ).…”
Section: Beyond the Neocortex: Nr2f1 Regulates The Anatomical And Functional Development Of The Hippocampusmentioning
confidence: 99%
“…Zhao et al (38) found a similar relationship between perifoveal retinal thickness and TBV in patients with AD and MCI, as well as with the entorhinal cortex and hippocampus. The same authors found a relationship between hippocampal volume and macular RNFL thickness and P100 amplitude measured by VEP (39).…”
Section: Resultsmentioning
confidence: 86%
“…Although retinal changes related to brain Aβ deposition have been documented using PET/CT (4), most of the studies used MRI. A relationship between the retinal structure and decreased brain volume has been reported for TBV (34,37,38) and the volume of particularly vulnerable regions, such as the hippocampus (38,39), entorhinal cortex (38), and parietal lobe (34). Regarding the relationship between the retina and brain visual pathways, an increment in WM hyperintensities has been reported in the occipital lobe (12), with a higher Aβ burden in V1 (3) and on DTI (40).…”
Section: Discussionmentioning
confidence: 96%
“…Different authors have reported reduced m-RNFL thickness in AD and MCI patients, associated with smaller hippocampal volumes and worse cognitive scores [ 50 ]. A delay in the latency time of the rod-cone response in the retina of both MCI and AD patients has also been found [ 50 ]. The presence of APOE ɛ4 in mice also induces both structural and functional retinal impairments [ 51 ].…”
Section: Discussionmentioning
confidence: 99%